Cadastre Grid Software: A GIS-tool for cadastre analysis connected to MapInfo GIS. - Vassilopoulos, A.; Evelpidou, N. (2001)
In this article, we will present the ‘Cadastre Grid Software’ (version 3) and its new enchanced functions and capabilities. This new version has already been used on a variety of applications, including archaeology (investigations on cadastre detection), geology (analysis on tectonic fault directions) and geomorphology (drainage system analysis). Moreover, we will describe the use of ‘Cadastre Grid Software’ in combination with MapInfo GIS, in order to extract primary data from maps (topographic, pedological, etc.), aerial photos and satellite images. Cadastre lines and grids extracted using the ‘Cadastre Grid Software’, are then processed with MapInfo GIS, enabling comparisons among different models or study areas, e.g. Bezier’s and Patra’s cadastres.